Impact of Aerobic Exercise and Yoga Asanas along with Diet Supplements on Haemoglobin Level among Female Collegiate: Life Sciences-Physiotherapy for Better Pain Management - G.Tharani; G.Preethi; K.Kamatchi; G.Yuvarani; G.Vaishnavi; S.Jenifer Augustina (International Journal of Life Science and Pharma Research, 2022)
Haemoglobin is a conjugate iron containing protein molecule in red blood cells that carries oxygen from the lungs to the body tissues and returns carbon dioxide from the tissues back to the lungs during all body functions. In India, anaemia is a widespread condition, due to lack of haemoglobin in children, non-pregnant women, and pregnant women. Anaemia increases the risk of death during pregnancy and leads to fatigue, poor motor and mental performance in adolescent girls. Recent literature also suggests an independent association of chronic anaemia with increased mortality in a variety of conditions including chronic kidney disease, heart failure, acute coronary syndromes and acute stroke. Hence, it is necessary to prevent the occurrence and progression of anaemia from mild to a severe form in young girls. Although the current medical management is effective in improving the Hb level, researches have found few adverse effects due to the high dose usage of such medications. Thus, this study intended to investigate the effects of aerobic exercise versus yoga along with diet supplement on the haemoglobin level. 20 female collegiate between 17 to 22 years with a BMI range of 20-25 kg/m2 and haemoglobin level from 8 to 11.5g/dl participated in this study. 10 subjects in Group A performed moderate intensity aerobic exercise and 10 subjects in Group B performed yoga asanas for 1 hour in the morning for 2 months after taking 5 grams jaggery and raisins. The result of this study suggested that both aerobic activity and yoga asanas along with raisins and jaggery helped to speed up the Hb synthesis and reduce mental and physical fatigue.